2021
DOI: 10.3390/nu13020467
|View full text |Cite
|
Sign up to set email alerts
|

Vagally Mediated Gut-Brain Relationships in Appetite Control-Insights from Porcine Studies

Abstract: Signals arising from the upper part of the gut are essential for the regulation of food intake, particularly satiation. This information is supplied to the brain partly by vagal nervous afferents. The porcine model, because of its sizeable gyrencephalic brain, omnivorous regimen, and comparative anatomy of the proximal part of the gut to that of humans, has provided several important insights relating to the relevance of vagally mediated gut-brain relationships to the regulation of food intake. Furthermore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Several studies have found that VNS promotes reduced food intake, causes weight loss, and reduces cravings and appetite [ 15 , 25 33 ]. VNS has been associated with reduced plasma glucose, cholesterol, visceral fat, and blood pressure [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that VNS promotes reduced food intake, causes weight loss, and reduces cravings and appetite [ 15 , 25 33 ]. VNS has been associated with reduced plasma glucose, cholesterol, visceral fat, and blood pressure [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Page summarises current knowledge about the transmission of gastrointestinal luminal, meal-related signals to the brain via the vagus nerve, the modulatory role of circadian rhythms on vagal responsiveness to luminal signals and the influences of obesity and light cycle disruptions—the latter simulating shift-work [ 12 ]. Malbert addresses vagally mediated gut–brain relationships, focusing on important insights derived from studies in pigs [ 13 ], particularly in relation to the sensing of information from the stomach, intestines and portal vein by vagal afferents and the central processing of this information, as evaluated by sophisticated imaging techniques. DiPatrizio summarises the evidence that supports an important modulatory role for endocannabinoids in transmitting signals along the gut-brain axis via direct and indirect interactions with vagal afferents [ 14 ].…”
mentioning
confidence: 99%